Amino acid metabolism in liver disease - Holm, Eggert; Sedlaczek, Oliver; Grips, Eva (Current opinion in clinical nutrition & metabolic care, 1999)
The impairment of transsulphuration during methionine degradation in hepatic failure can be counteracted by treatment with S-adenosylmethionine. Regarding the pathogenesis of hepatic encephalopathy, no convincing evidence exists for tryptophan, glutamine or glutamate being involved. Portal-systemic shunting-induced hyperammonaemia may reduce plasma branched-chain amino acids. The glucose effect on urea synthesis does not exist in cirrhosis.